2021
DOI: 10.1515/med-2021-0220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of therapeutic plasma exchange in stiff person syndrome

Abstract: The stiff person syndrome (SPS) is an extremely rare neurological disorder with primarily immune-mediated etiology. The cardinal symptoms are progressive, fluctuating axial/proximal limb muscle stiffness and spasms. The diagnosis is based on the clinical picture, electromyography examination and detection of antibodies to glutamic acid decarboxylase (anti-GAD). Adverse effects of medications might preclude its use or increase in dosing, therefore symptomatic and/or immunomodulatory medical therapy might be ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…However, there is a lack of consensus on the immunotherapy regimen. A study showed that IVIG had a better therapeutic effect than IVMP for patients with SPS and ACA ( 24 ). Another study found that corticosteroids were the best regimen for ACA ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of consensus on the immunotherapy regimen. A study showed that IVIG had a better therapeutic effect than IVMP for patients with SPS and ACA ( 24 ). Another study found that corticosteroids were the best regimen for ACA ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our review showed that 83.16% of the patients receiving IVIG had some form of improvement demonstrated either through various scoring systems or subjectively. While comparing the efficacy of IVIG therapy with plasma exchange, a review by Czempik et al revealed that 70% (n = 28) showed marked improvement, while 30% showed no improvement, among 40 patients receiving therapeutic plasma exchange 69 . GABA is involved in a number of synaptic transmissions in the brain that control muscle tone, autonomic responses, fear, arousal, and behavior 58 .…”
Section: Discussionmentioning
confidence: 99%
“…showed no improvement, among 40 patients receiving therapeutic plasma exchange. 69 GABA is involved in a number of synaptic transmissions in the brain that control muscle tone, autonomic responses, fear, arousal, and behavior. 58 Increased GABAergic transmission due to the use of IVIG results in decreased muscle stiffness as well as a decrease in the frequency of spasms triggered by fear and emotional upsets in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a small randomized controlled trial with 16 patients who had SPS and anti-GAD Abs, intravenous immunoglobulins (IVIGs) were effective in reducing spasms and improving functional outcomes (13). A recent study suggested the safety and efficacy of therapeutic PLEX as an adjunct to immunosuppressive therapy in GAD Ab-associated SPS (14). However, in paraneoplastic SPS, randomized controlled trials are lacking due to the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%